Laparoscopic ovariectomy in a dog with type III sclerosing encapsulating peritonitis and literature review - Brückner, Michael; Bogisch, Sandra (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2022)
Sclerosing encapsulating peritonitis is a rare and not well-recognized disease in veterinary medicine. A 14-month-old female intact mixed-breed dog was diagnosed with sclerosing encapsulating peritonitis (SEP) at the age of 5 months after a routine work-up including biopsies from an exploratory laparotomy. Symptomatic treatment with an immunosuppressive dose of prednisolone was started, but dose reduction was unsuccessful. Combined treatment with tamoxifen, a selective estrogen receptor modulator used for its TGF-β1 suppression of fibroblasts was discussed; the owner was informed about the risk for developing a pyometra. About one year later the owner wanted to spay her dog and an ovariectomy was recommended, especially due to the extensive adhesions. A laparoscopic approach was chosen to reduce the amount of intraoperative tissue manipulation and inflammation, as well as to minimize the size of the incision. The dog continues to be doing well one year after surgery and prednisolone could be reduced to a low maintenance dose after surgery; so far, the addition of tamoxifen was not required. In selected cases, laparoscopy appears as a safe alternative in patients with adhesions, but the surgeon should always be prepared to convert in case of impaired vision, especially in the absence of tactile sensation. This case report is the first description of laparoscopy in a dog with SEP. Laparoscopy may serve as an easily accomplished minimally invasive method to diagnose SEP, but further studies are required.
Keywords: Sclerosing peritonitis; laparoscopy; canine; ovariectomy